2009
DOI: 10.1017/s0022149x09990381
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and molecular characterization of Strongyloides ophidiae (Nematoda, Strongyloididae)

Abstract: The aim of the present study is to report morphological data from parasitic female, rhabditoid and filarioid larvae, free-living female worms and eggs of Strongyloides ophidiae (Nematoda, Strongyloididae). In addition, a molecular DNA analysis was carried out using a pool of eight S. ophidiae parasitic females. Samples were obtained from the small intestine of Oxyrhopus guibei (Serpentes, Colubridae) collected in the municipality of Lençó is Paulista, State of São Paulo, Brazil. DNA amplification by polymerase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 12 publications
0
14
0
2
Order By: Relevance
“…The genus Strongyloides contains more than 40 species of parasitic monoxenous nematodes (Grove, 1989) that mainly infect mammals, and more occasionally reptiles, amphibians and birds (Dorris et al , 2002; Viney & Lok, 2007). Among reptiles, although snakes are the group most commonly infected (Pereira, 1929; Holt et al , 1979; Dos Santos et al , 2010), geckos ( Hemydactylus mabouia , Rodrigues, 1968) and lacertids ( Podarcis pityusensis , Roca & Hornero, 1992) have also been reported as hosts. The screening of tissue samples in this study has revealed the presence of Strongyloides in a new host, the lacertid lizard P. lilfordi .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The genus Strongyloides contains more than 40 species of parasitic monoxenous nematodes (Grove, 1989) that mainly infect mammals, and more occasionally reptiles, amphibians and birds (Dorris et al , 2002; Viney & Lok, 2007). Among reptiles, although snakes are the group most commonly infected (Pereira, 1929; Holt et al , 1979; Dos Santos et al , 2010), geckos ( Hemydactylus mabouia , Rodrigues, 1968) and lacertids ( Podarcis pityusensis , Roca & Hornero, 1992) have also been reported as hosts. The screening of tissue samples in this study has revealed the presence of Strongyloides in a new host, the lacertid lizard P. lilfordi .…”
Section: Discussionmentioning
confidence: 99%
“…The lack of sequences from other Strongyloides species infecting reptiles prevents confirmation of host-specificity within this group. However, an assessment including a short fragment (323 bp) in GenBank available for a species infecting a snake ( S. ophididae , accession number EU287935, Dos Santos et al , 2010 – analysis not shown) indicates that the two sequences available from Strongyloides species infecting reptiles and the one from Strongyloides sp. infecting frogs are part of the same clade.…”
Section: Discussionmentioning
confidence: 99%
“…Podem ocasionar úlceras hemorrágicas, inflamação severa, anemia, peritonite, infecções secundárias e fezes muco-sanguinolentas (Klingenberg, 1993;Dias et al, 2004). Pinto et al (2010) observaram o parasito Kalicephalus costatus no intestino de uma serpente da espécie Crotalus durissus, a qual pertencia a um sistema semi-intensivo de cativeiro no Brasil, assim como Silva et al (2001). A espécie K. inermis foi reportada no estômago de outro exemplar desta serpente, neste caso, de vida livre.…”
Section: Helmintosunclassified
“…Esta sintomatologia é somente observada em animais com infecção bacteriana secundária, decorrente de um alto grau de parasitismo, estresse, higiene inadequada e umidade relativa e temperatura elevadas (Klingenberg, 1993;Luppi et al, 2007). Luppi et al (2007) Siqueira et al (2009), e em Crotalus durissus de sistema semi extensivo (Silva et al, 2001).…”
Section: Helmintosunclassified
“…Under indirect development, the rhabditiform larvae develop into either males or females. Postembryonic development of Strongiloides has distinct morphological traits by which its stages are identified (Lyons et al, 1973;Dewes and Townsend, 1990;Grant et al, 2006;Viney, 2006;Santos et al, 2010;Thamsborg et al, 2016).…”
Section: Introductionmentioning
confidence: 99%